Cellular populations and sclerosis factors at limited scleroderma on the edema stage: immunohistochemical research - Romanenko K.V. (Морфологія, 2009)
The purpose of the current study was to reveal immunohistochemical features of derma and epidermis in the edema stage of localized scleroderma using markers: CD3, CD8, CD20, CD79α, CD68, CD1α, CD34, CD105, SMA, vimentin, eNOS, Ki67, collagen IV, bcl2, caspase 3. T-lymphocytes (20-40%), among last supressors, and the immature forms of B-lymphocytes (20-40%) prevail in perivascular infiltrates and mononuclear accumulations around the appendages of skin during this stage. There are macrophages in infiltrates (to 30%). Activity of eNOS in endothelium of vessels is increased. The CD105 synthesis was observed in dermal dendrocytes, immune cells of infiltrates and in single macrophages. The latters give the most number of CD105+ among immune cells. Amount of CD34+ dendrocytes was reduced, in the same time Lanhgergan’s cells (CD1α+), vimentin+ and SMA+ of dendrytic cells was multiplied. The change of cellular composition was more substantial in areas round the appendages. The active immune inflammation leads to the local promoted proliferation and apoptotic activity, and similarly to activation of the antіapoptotic programs. Thus, the edema stage of localized scleroderma is related to the most active changes both from the side of the immune system and by local alterations of skin tissues.